Climate change-related regulatory risks and bank lending - Isabella Mueller; Eleonora Sfrappini (European Central Bank (ECB), 2022)
We identify the effect of climate change-related regulatory risks on credit reallocation, Our evidence suggests that effects depend borrower's region, Following an increase in salience of regulatory risks, banks reallocate credit to US firms that could be negatively impacted by regulatory interventions, Conversely, in Europe, banks lend more to firms that could benefit from environmental regulation, The effect is moderated by banks' own loan portfolio composition, Banks with a portfolio tilted towards firms that could be negatively affected by environmental policies increasingly support these firms, Overall, our results indicate that financial implications of regulation associated with climate change appear to be the main drivers of banks' behavior.
Keywords: G21; Q51; Q58; 330; climate change; climate risk; credit reallocation; Paris Agreement